FAKTOR RISIKO STUNTING PADA WILAYAH KRISIS AIR DI KECAMATAN PONTANG, KABUPATEN SERANG, BANTEN - Meliana Sari (IAKMI South Tangerang Branch, 2023)
Abstract Background: Stunting is one of the problems of child development and growth. Clean water, hygiene, and sanitation are indirect factors that play a role in stunting. Pontang Sub-District, Serang Regency was included in the National Stunting Management Locus in 2021. Another challenge is Pontang Sub-District is predicted to have a clean water crisis in the low to high category. Objective: To determine the relationship between risk factors and the incidence of stunting in Pontang Sub-District. Method: This research was conducted in Domas Village and Pontang Village, Pontang Sub-District, Serang Regency. Data were collected in July 2022. This research used a case-control study design, with a sample size of 47 people from each case and control group. Data were collected using questionnaires and environmental observation sheets using a purposive sampling method. Data analysis used the Chi-Square Test and Odds ratio (OR). Results: The results of the study found that there was a relationship between clean water (OR = 2.8; 95% CI 1.171-6.672), sanitation (OR = 2.84; 95% CI 1.232-6.563), exclusive breastfeeding (OR = 7.35; 95% CI 1.59-8.81) and giving MP-ASI (OR = 2.62; 95% CI 1.029-6.674) with the incidence of stunting. Hygiene, growth and development monitoring, and a history of infectious diseases are not related to the incidence of stunting. Conclusion: Increasing access to clean water, improving sanitation, and education regarding breastfeeding and MP-ASI need to be improved to reduce the incidence of stunting in the Pontang District area. Keywords: Stunting, Breastfeeding, WASH Abstrak Latar belakang: Salah satu masalah yang menjadi tantangan di fase pertumbuhan dan perkembangan anak adalah stunting. Diantara banyak faktor, ketersediaan air bersih, higiene dan sanitasi adalah faktor tidak langsung yang berperan dalam kejadian stunting. Kecamatan Pontang Kabupaten Serang masuk dalam lokus penanganan stunting Nasional tahun 2021. Tantangan lainnya, Kecamatan Pontang diprediksi mengalami krisis ketersediaan air bersih kategori rendah hingga tinggi. Tujuan: Mengetahui hubungan faktor risiko dengan kejadian stunting di Kecamatan Pontang. Metode: Penelitian ini dilakukan di Desa Domas dan Desa Pontang Kecamatan Pontang Kabupaten Serang. Data dikumpulkan pada bulan Juli 2022. Penelitian ini menggunakan desain studi case-control, dengan jumlah sampel sebanyak 47 orang pada masing-masing kelompok kasus dan kontrol. Pengumpulan data menggunakan lembar observasi lingkungan dan kuesioner melalui pendekatan metode purposive sampling. Analisis data menggunakan Uji Chi-Square dan Odds ratio (OR). Hasil: Hasil penelitian ditemukan terdapat hubungan antara ketersediaan air bersih (OR = 2,8; 95% CI 1,171-6,672), sanitasi (OR = 2,84; 95% CI 1,232-6,563), ASI Eksklusif (OR = 7,35; 95% CI 1,59-8,81) dan Pemberian MP-ASI (OR = 2,62; 95% CI 1,029-6,674) dengan kejadian stunting. Adapun higiene, pemantauan tumbuh kembang dan riwayat penyakit infeksi tidak berhubungan dengan kejadian stunting. Kesimpulan: Peningkatan akses ketersediaan air bersih, perbaikan sanitasi dan edukasi mengenai ASI dan MP-ASI perlu ditingkatkan untuk menurunkan kejadian stunting di wilayah Kecamatan Pontang. Kata kunci: Stunting, ASI Eksklusif, Air, Sanitasi, Higiene